INSULIN RESISTANCE IN PATIENTS WITH DIABETES MELLITUS OF TYPE 2 WITH NORMAL BODY WEIGHT - Парцхаладзе В. І. (World of Medicine and Biology, 2014)
For persons with normal body, mass existing anthropometric markers that no suggest abdominal obesity (AO) and insulin resistance (IR), at the same time demonstrative is can be methods of laboratory diagnosis. The aim of this study was to determine the index insulinorezistentnosti (HOMA-IR) in patients with type 2 diabetes with normal weight (normW) and establish the predictive value of waist circumference values in these patients as an indicator of AO.Index of IR and index HOMA-IR are calculated for patients with clinical phenotype of type 2 diabetes with normW, overweight (overW) and obesity (OB).It was established that, this index has been raised in the subgroups with different BMI, and, it was the highest for patients with normW and authentically higher than for patients with n overW due to authentically higher hyperglycemia.In subgroups with increased HOMA-IR proportion of persons with an increased waist (according to the criteria IDF) was authentically lower at normW, amounting to just 42.2%, ie for this group of patients with diabetes record from can not be used as a prognostic on the development of IP. For patients with type 2 diabetes with normW, as well as for patients with overW and OB, characterized by the development of IP. Monitoring of patients with type 2 diabetes with normal body weight requires the provision of measures to reduce IP. Given the high incidence of insulin resistance in this group of patients with type 2 diabetes with normW, is expanded to indications for therapeutic intervention with the use of groups of drugs that increase insulin sensitivity, which determines the prospects for further research in this direction.
Keywords: diabetes; a normal body weight; insulin resistance